Salinity impact on ammonia oxidizers activity and amoA expression in estuarine sediments. (31st October 2018) - Santos, J.P.; Mendes, D.; Monteiro, M.; Ribeiro, H.; Baptista, M.S.; Borges, M.T.; Magalhães, C.
Abstract: In this study, we investigated the effect of simulated salinities in the nitrification process in estuarine sediments through fingerprinting analysis of ammonia-oxidizing archaea (AOA) and Betaproteobacteria (β-AOB) amoA genes transcription, isotopic measurements of total and selective (AOA and AOB) nitrification rates, and inorganic nitrogen fluxes. Results revealed that ammonia oxidizers adapted to distinct estuarine salinity regimes exhibited different responses in terms of total nitrification activity when facing salinity changes of 0, 15 and 30, with the downstream sediments displaying higher plasticity towards salinity increment (0.058, 0.117 and 0.123 nmol N g −1 h −1 mL −1, respectively), while the upstream sediments displayed a decrease in potential nitrification rates as a consequence of salinity increment (0.472, 0.378, 0.179 nmol N g −1 h −1 mL −1, respectively). In addition, our findings demonstrated that salinity is an important variable in controlling the selection of the group of organisms (archaea or bacteria ammonia oxidizers) that mediated the nitrification process in estuarine systems. We believe that results from this study are critical to understand the response of estuarine nitrifier communities to different salinity regimes. Graphical abstract: